2021
DOI: 10.1016/j.sdentj.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical study comparing Piezoelectric Surgery with conventional rotatory osteotomy in mandibular third molars surgeries

Abstract: Purpose The aim of this study was to evaluate the performance and to assess the postoperative sequel and quality of life after removal of impacted mandibular third molars using piezoelectric surgery compared with conventional rotatory osteotomy. Patients and methods A single blinded, randomized, control clinical study was performed. Sixty-three patients (44 males, 19 females) who presented with bilaterally asymptomatic impacted mandibular third molars were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
0
21
0
3
Order By: Relevance
“…Scarano and colleagues 32 randomly assigned 30 cases into two groups, which were given lateral window SFE respectively by traditional rotary instruments or piezoelectric tools, finding significantly higher SMP rate in the rotary instrument group. Because piezoelectric tools conduct osteotomy by low‐frequency ultrasonic vibration, allowing precise ectomy of bone tissue without injuring soft tissue like sinus membrane 33 . In a recent meta‐analysis, 25 the SMP rate of traditional instruments was estimated to be 24%, while that of piezoelectric tools being 8%, with statistical significance ( p < 0.05), which proves that application of piezoelectric tools could rescue the risk of SMP.…”
Section: Discussionmentioning
confidence: 98%
“…Scarano and colleagues 32 randomly assigned 30 cases into two groups, which were given lateral window SFE respectively by traditional rotary instruments or piezoelectric tools, finding significantly higher SMP rate in the rotary instrument group. Because piezoelectric tools conduct osteotomy by low‐frequency ultrasonic vibration, allowing precise ectomy of bone tissue without injuring soft tissue like sinus membrane 33 . In a recent meta‐analysis, 25 the SMP rate of traditional instruments was estimated to be 24%, while that of piezoelectric tools being 8%, with statistical significance ( p < 0.05), which proves that application of piezoelectric tools could rescue the risk of SMP.…”
Section: Discussionmentioning
confidence: 98%
“…In 2019, Gumrukcu et al also performed a retrospective clinical study to compare the post-operative effects of the conventional surgery, piezo surgery technique and submucosal dexamethasone injection in lower third molars extractions, and concluded that dexamethasone was effective in reducing swelling, pain, mouth opening restriction, and that Piezosurgery has positive effects on pain, swelling, trismus, and number of used analgesics compared to the control group [ 28 ]. In 2021, Al-Delayme et al compared piezo-electric surgery with conventional and concluded that piezosurgery reduces postoperative pain, trismus, and swelling [ 51 ]. Furthermore, Gulnahar et al compared postoperative morbidity between piezoelectric surgery and conventional rotary instruments in mandibular third molar surgery, and concluded that piezosurgery is a safe alternative method that can be used for the removal of impacted mandibular third molars, but did not provide a significant benefit in terms of postoperative pain and trismus [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through this window, with the proper selection of the instruments, the alveolar bone will be retained to the greatest extent and the bone damage will be reduced. 15,16 Extraction of impacted teeth based on the concept of bone preservation can effectively reduce bone damage. In order to protect the alveolar bone as much as possible, we can increase the gap inside the tooth, to transfer the space needed for extraction of impacted teeth to the inside of the tooth, which would provide enough space by removing/ grinding the unnecessary tooth tissue.…”
Section: Discussionmentioning
confidence: 99%
“…There is a window around the crown of the impacted teeth or even around the neck of the teeth. Through this window, with the proper selection of the instruments, the alveolar bone will be retained to the greatest extent and the bone damage will be reduced 15,16 …”
Section: Discussionmentioning
confidence: 99%